Solid particle erosion behavior of thermal barrier coatings produced by atmospheric plasma spray technique - Kaplan, Mustafa; Uyaner, Mesut; Avcu, Egemen; Avcu, Yasemin Yildiran; Karaoğlanlı, Abdullah Cahit; Karaoğlanlı, Abdullah Cahit (Taylor & Francis Inc, 2019)
Thermal barrier coatings (TBCs) are commonly applied specifically for aerospace applications in which they are subjected to air-borne particles. Therefore, solid particle erosion behavior of all coating layer has been an important phenomenon and erosion behavior of various TBCs has been widely investigated in literature. In the present study, CoNiCrAlY and yttria stabilized zirconia (ZrO2 + 8% Y2O3) powders were deposited on Inconel 718 nickel based super alloy substrate. Atmospheric plasma spraying technique was applied for the deposition of the metallic bond coat and the ceramic top coats. Erosion tests were carried out under various particle impingement angles with an air jet erosion tester. Afterwards, eroded surfaces of the specimens were investigated with a three-dimensional (3D) optical surface profilometer (noncontact) and scanning electron microscope. The erosion rates, the areal surface roughness values, the 3D surface topographies, and the surface morphology of the specimens were evaluated based on the particle impingement angle to understand the solid particle erosion behavior of the produced coatings. The maximum erosion rates occurred at 60 degrees impingement angle which is an indication of semi-ductile/semi-brittle erosion behavior. Furthermore, the surface roughness values and surface topographies also dramatically varied depending on the impingement angle. Deeper and wider erosion craters formed at 60 degrees impact angle and the erosion craters were visualized by profilometer analysis.
Keywords: Thermal Barrier Coatings (Tbcs); Atmospheric Plasma Spray (Aps); Solid Particle Erosion; Erosion Mechanisms; Surface Roughness; Surface Topography